Population genetic study of 34 X-Chromosome markers in 5 main ethnic groups of China - Zhang, Suhua (Sci Rep, 2015)
As a multi-ethnic country, China has some indigenous population groups which vary in culture and social customs, perhaps as a result of geographic isolation and different traditions. However, upon close interactions and intermarriage, admixture of different gene pools among these ethnic groups may occur. In order to gain more insight on the genetic background of X-Chromosome from these ethnic groups, a set of X-markers (18 X-STRs and 16 X-Indels) was genotyped in 5 main ethnic groups of China (HAN, HUI, Uygur, Mongolian, Tibetan). Twenty-three private alleles were detected in HAN, Uygur, Tibetan and Mongolian. Significant differences (p < 0.0001) were all observed for the 3 parameters of heterozygosity (Ho, He and UHe) among the 5 ethnic groups. Highest values of Nei genetic distance were always observed at HUI-Uygur pairwise when analyzed with X-STRs or X-Indels separately and combined. Phylogenetic tree and PCA analyses revealed a clear pattern of population differentiation of HUI and Uygur. However, the HAN, Tibetan and Mongolian ethnic groups were closely clustered. Eighteen X-Indels exhibited in general congruent phylogenetic signal and similar cluster among the 5 ethnic groups compared with 16 X-STRs. Aforementioned results proved the genetic polymorphism and potential of the 34 X-markers in the 5 ethnic groups.